Review PaperGenetic aspects of food allergy - Pałgan, Krzysztof; Bartuzi, Zbigniew (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
The increasing prevalence of food allergy is a growing problem. This review examines recent developments in the genetic factors of food allergy. The use of genomic information, accelerated by the sequencing of the human genome and the advent of new tools and technologies, has raised widespread hope that food allergy genetics can significantly contribute to the prediction, prevention, and treatment of food allergy.